Model Persebaran Emisi pada Pembangkit Listrik Tenaga Uap Berbahan Bakar Serat dan Cangkang Kelapa Sawit Menggunakan Perangkat Pemodelan Aermod - Ira Galih Prabasari; Niken Pusparani (Universitas Batanghari Jambi, 2022)
According to the Republic Indonesia government regulation to reduce greenhouse gas emissions by 29% independently and 41% with international assistance in 2030, then to achieve the target of net zero emissions by 2060 in accordance with the COP27 Climate Change Conference in Egypt in 2022, it is necessary to found renewable energy sources with low emission levels. Renewable energy sources with low emission levels that are quite popular and available are those from palm oil waste biomass such as oil palm empty fruit bunches, fibre and oil palm shells. This study aimed to determine the emission dispersion modelling from the combustion of fibre and palm kernel shells mixture with ratio 60% and 40% at two steam power plants with a capacity of 30 tons/hour and 20 tons/hour, respectively, using Aermod Modelling System. The emission load calculated using combustion mass balance calculation method. Mass balance calculation result showed that the emission content from the two chimneys is 134.76 mg/m3 for the NO2 parameter; 13.11 mg/m3 for the SO2 parameter and 37.31 mg/m3 for the particulate parameter. Meanwhile, for emission dispersion, the highest emission level occurs at coordinates X = 200319.12 and Y = 9817175.03, which is the closest coordinate to the emission source where the highest value at that location for the NO2 parameter is 241.18 µg/m3, the SO2 parameter is 15.29 µg/m3 and particulate parameters of 66.91 µg/m3. The distribution of emission dispersion tends to be southeast and north according to the wind direction at the study site..